Large carnivore damage in Europe: Analysis of compensation and prevention programs. (July 2019) - Bautista, Carlos; Revilla, Eloy; Naves, Javier; Albrecht, Jörg; Fernández, Néstor; Olszańska, Agnieszka; Adamec, Michal; Berezowska-Cnota, Teresa; Ciucci, Paolo; Groff, Claudio; Härkönen, Sauli; Huber, Djuro; et al.
Abstract: The mitigation of conflicts associated with large carnivore damage to livestock and agriculture is pivotal to their conservation. We evaluate current programs to compensate and prevent large carnivore damage in 27 European countries and the factors related to the economic costs of these programs. Overall, high compensation costs are associated with free-ranging livestock (68% of total costs) and with national economic wealth. Contrary to general belief, the return of large carnivores does not always translate into higher compensation costs. We identify a tendency towards prioritizing compensation over prevention; only a few wealthy countries pay the majority of the money allocated for prevention programs to adapt husbandry practices to the presence of large carnivores. We conclude that programs mainly focused on paying large compensation amounts will often fail to build tolerance towards predators. To mitigate conflicts and optimize the cost-effectiveness of publicly funded measures, responsible agencies should be proactive, focus on prevention-based policies and periodically evaluate the effectiveness of compensation and prevention programs in an adaptive manner. With this purpose and to identify further solutions for conflict mitigation, we call for a pan-European database of damage occurrence, management actions and associated costs. Highlights: Wealthy countries tend to spend more to compensate large carnivore damage in Europe. High compensation and prevention costs are associated with free-ranging livestock. Large carnivores' return does not always translate into high compensation costs. Only few European countries subsidize preventive measures on a regular basis. Compensation alone will often fail to build tolerance towards predators.